Estimation and characterization of prostaglandins in the human gastrointestinal tract - Bennett, A. (1977)
1 Prostaglandin-like material was extracted from muscle and mucosa of surgically removed human stomach, ileum and colon and assayed against prostaglandin E(2) on strips of rat gastric fundus. Superfused human isolated gastric mucosa released prostaglandin-like material and release was increased by stretching or clamping the tissue. 2 The relative amounts of extracted biological activity were broadly as follows: gastric antral mucosa > colon muscle > gastric body mucosa ≈ ileal mucosa > colon mucosa ≈ gastric muscle ≈ ileal muscle. 3 Prostaglandin E and F were tentatively identified by chromatography and sensitivity to inactivation by alkali. 4 Prostaglandin E apparently contributed most to the biological activity, possibly because the assay tissue is more sensitive to prostaglandin E than to F. Chromatography of gastric body mucosal extracts located material running with prostaglandin E(2) and a little with E(1). Colonic muscle and mucosal extracts contained material with R(F) values of prostaglandins E(1), E(2), E(3) and F(1a), whereas F(2a) and F(3a)-like substances were found only in the mucosa. The proportions of prostaglandin F varied between specimens. 5 The amount of extracted prostaglandin-like activity was increased by adding cofactors and arachidonic acid, and lessened by homogenization with acid-ethanol. 6 The type and amount of activity generated from arachidonic acid by partly purified colonic mucosal prostaglandin synthetase depended on the substrate concentration. 7 The possible relationships of prostaglandins to mucus secretion and other physiological and pathological gut functions are discussed.